Analysis of the Spatial Error Model with Queen Contiguity Matrix Weights on Dengue Fever - Soraya, Siti; Aziza, Istin Fitriani; Arisandi, Rizwan; Verma, Kirti; Isasi, Widani Darma; Sufahani, Suliadi Firdaus (Universitas Muhammadiyah Mataram, 2026)
Dengue Fever is one of the deadly diseases caused by a rapidly spreading virus transmitted through the Aedes aegypti mosquito. This study focuses on the NTB region, which has different geographical characteristics and infrastructure challenges. The variables used in this study are: dengue fever incidence, population, hospitals, community health centers, poor residents, and floods. The aim of this study is to model the factors that influence the occurrence of dengue fever in NTB. The method used is the Spatial Error Model (SEM), which serves to analyze spatial data to observe spatial correlation in the error variables. The research results indicate that the Moran Index and the Lagrange Multiplier test confirm the existence of spatial dependence in the error aspects. Significant variables at the 5% level affecting dengue fever cases are population size, the number of hospitals, and the number of community health centers. These findings provide an important scientific contribution as they represent one of the early studies that specifically identify and model the spatial dependence patterns of dengue fever cases in West Nusa Tenggara using a spatial econometric approach, thereby enriching the literature on spatial epidemiology at the regional level. The findings indicate that population growth and disparities in healthcare facilities increase the risk of dengue fever. This implies that more equitable spatial planning of healthcare services, strengthening of primary care, population density control, and increased community participation in sanitation and regular mosquito breeding site eradication are necessary as part of an to reduce dengue fever cases in NTB.